Predicting the brighter and darker sides of interpersonal relationships: Does psychological need thwarting matter? - Costa, S.; Ntoumanis, Nikos; Bartholomew, K. (Springer Netherlands, 2014)
Recent studies have indicated that assessments of need thwarting better predict diminished functioning and ill-being compared to low need satisfaction, which better predict optimal functioning and well-being. In this study we aimed to further explore the important theoretical distinction between psychological need thwarting and need satisfaction in the domain of interpersonal relationships. We examined whether the distinction between need satisfaction and thwarting is due to method effects resulting from positive and negative item wording, however, multi-trait multi-method analyses indicated no substantial method effects. Further, we showed that a lack of need satisfaction (i.e., need dissatisfaction) is not equivalent to experiences of need thwarting. In fact, need thwarting better predicted compromised relational functioning compared to need dissatisfaction. Need satisfaction was a stronger predictor of interpersonal competence compared to need thwarting and need dissatisfaction. The current findings underline the importance of assessing need thwarting when examining compromised functioning in interpersonal relationships.